Characterisation of production, marketing and consumption patterns of farmed tilapia in the Nile Delta of Egypt - Eltholth, Mahmoud; Fornace, K.; Grace, Delia; Rushton, Jonathan; Häsler, Barbara (Elsevier, 2015)
Egypt has one of the world’s largest aquaculture sectors which makes a significant contribution to income, employment creation and food security. However, there are very limited data available on the farmed tilapia value chain. The aim of this study therefore was to characterise production, marketing and consumption patterns of farmed tilapia in the Nile Delta of Egypt. A cross sectional study was conducted to collect data from tilapia producers (100), transporters (32), retailers (100), fish fry shops (20) and households (300) in three case study communities (fish producing, peri-urban and rural community). We conducted structured questionnaire interviews and participatory assessments for producers and consumers. Focus group discussions with mothers were also held to collect data for the availability, sources and consumption patterns of tilapia. Results showed that, more than half of producers were small scale, having a farm size of 10 feddan or less (1 feddan = 4200 m2). The main water supply for almost all farms was agricultural drain water, a potential source of contamination with chemical and biological hazards. The main production constraints were reported to be feed prices, water quality and availability, land rent, fuel and energy sources and environmental conditions. The farmed tilapia value chain was short with some value added in the form of marketing fresh and live fish as well as selling tilapia in fried or grilled form. The majority of produced tilapia was transported to retail sale and sold to consumers as fresh, while only a small proportion was processed by cleaning, grilling or frying. A lack of hygiene during transportation and marketing of farmed tilapia was found that could be potential sources for post-harvesting contamination. The availability and frequency of tilapia consumption were higher in the community in the production areas than in other communities. In non-producing areas, tilapia may be available in the market once a week during the village market day. Potential areas for further research in order to improve safety, quality and production of farmed tilapia were identified.